Biopsy of lung lesions under CT control - Marel, Miloslav; Padr, Radek; Fila, Libor; Rakita, Dmitry; Casas Mendez, Fernando; Capkova, Linda; Capek, Vaclav; Pavlik, Radim (Biomedical papers, 2021)
Objectives. With the increasing number of detected lung nodules and the need for morphological verification, the number of CT- controlled biopsies is increasing. The aim of this study was to assess the risks and benefits of these biopsies. Methods. This is a prospective and observational study. We evaluated 101 punctures performed on a group of 90 consecutive patients in the Department of Radiology. Results. In patients with a mean age of 66 years, with mostly accidentally detected lung nodules, we observed complications 38 times. The most common were minor pneumothoraxes or insignificant bleedings. In 6 patients, the complications were more serious, 5 times the pneumothoraxes required chest drainage, once massive hemoptysis was recorded. The lesions were successfully biopsied 78 times, the target was missed 23 times. The diagnosis of lung cancer (LC) was confirmed in 60 patients, 49 LCs were verified by puncture under CT control. 42% (25/60) of patients with LC were diagnosed in TNM stages I and II. 23% (14/60) of patients with LC were treated surgically. The remaining 30 patients most often suffered from lung metastazes (13/30), in 8 of them an inflammatory lung disease was diagnosed. 69 patients underwent bronchoscopy, in only 19% (13/69) it contributed to the diagnosis. In a model "screening like" group of 49 patients with only randomly detected lung deposits, we diagnosed LC in 76% (37/49). 49% (18/37) were in TNM stage I and II, 11 were treated surgically. Conclusions. CT-controlled biopsy of lung lesions is an effective and safe diagnostic method.
Keywords: CT-controlled biopsy; lung nodules; lung cancer